a的平方b-b的平方c+c的平方a-a的平方c+b的平方a+c的平方b-2abc因式分解

来源:学生作业帮助网 编辑:作业帮 时间:2024/04/29 21:49:12
a的平方b-b的平方c+c的平方a-a的平方c+b的平方a+c的平方b-2abc因式分解

a的平方b-b的平方c+c的平方a-a的平方c+b的平方a+c的平方b-2abc因式分解
a的平方b-b的平方c+c的平方a-a的平方c+b的平方a+c的平方b-2abc因式分解

a的平方b-b的平方c+c的平方a-a的平方c+b的平方a+c的平方b-2abc因式分解
a^2b+a^2c+ab^2+b^2c+ac^2+bc^2+2abc
= a^2b+a^2c+ab^2+ abc +b^2c+ac^2+bc^2+abc
=(a^2b+a^2c+ab^2+ abc )+(b^2c+ac^2+bc^2+abc)
=(a^2b+a^2c+ab^2+ abc )+(b^2c+ac^2+bc^2+abc)
=[a(ab+ac+b^2+ bc)]+[c+( b^2+ac+bc+ab)]
=(ab+ac+b^2+ bc)(a+c)
=(a+ b)(b+c)(a+c)